Sistem Pendukung Keputusan Untuk Dispensasi Pembayaran Uang Kuliah - Poningsih Poningsih; Sundari Retno Andani (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2018)
STIKOM Tunas Bangsa give facility to some students in tuition payment to the underprivileged students in economic but they achieve. For the convenience, it must suitable with applicable criteria established by the Institution. Because of the large number of students who apply for the tuition free dispensation was very much, it is necessary to build a decision support system to give a decision or recommendation associated with the tuition payment dispensation. This decision support system use fuzzy logic that will help STIKOM Tunas Bangsa Institution in determining who is eligible to receive a tuition free dispensation as well as a large percentage of tuition free delays. The criteria that established in this case study was the large of parents income, the number of parental dependent, the number of sibling. Not all who apply for dispensation will be accepted, but only those who meet the criteria will be accepted.